2016
DOI: 10.1038/srep22405
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Sipjeondaebo-tang Alleviates Memory Deficits and Loss of Hippocampal Neurogenesis in Scopolamine-induced Amnesia in Mice

Abstract: We investigated the anti-amnesic effects of SJ and fermented SJ (FSJ) on scopolamine (SCO)-induced amnesia mouse model. Mice were orally co-treated with SJ or FSJ (125, 250, and 500 mg/kg) and SCO (1 mg/kg), which was injected intraperitoneally for 14 days. SCO decreased the step-through latency and prolonged latency time to find the hidden platform in the passive avoidance test and Morris water maze test, respectively, and both SCO effects were ameliorated by FSJ treatment. FSJ was discovered to promote hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…This assay was conducted in a 96-well plate, and each reaction contained a 100 μL sample, 50 μM acetylcholine, 200 μM Amplex Red reagent, 0.1 U/mL choline oxidase, and 1 U/mL horseradish peroxidase (HRP) in reaction buffer. The reaction systems were incubated at room temperature for 20 min with protection from light, and then fluorescence intensity was measured at the excitation wavelength of 560 nm and the emission wavelength of 580 nm [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…This assay was conducted in a 96-well plate, and each reaction contained a 100 μL sample, 50 μM acetylcholine, 200 μM Amplex Red reagent, 0.1 U/mL choline oxidase, and 1 U/mL horseradish peroxidase (HRP) in reaction buffer. The reaction systems were incubated at room temperature for 20 min with protection from light, and then fluorescence intensity was measured at the excitation wavelength of 560 nm and the emission wavelength of 580 nm [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fermented Bozhougyiqi-tang (78), Gumiganghwal-tang (79,80), and Hwangryunhaedok-tang (81) showed more potent protective activities against glutamate-stimulated cell death in HT22 cells than the unfermented prescription. Moreover, several studies in scopolamine-treated mice reported that fermented Sipjeondaebo-tang (82), Bozhougyiqi-tang (78), and Gumiganghwal-tang (79,80) significantly ameliorated amnesic behaviors possibly through AChE inhibition. These results suggest that fermentation might improve the pharmacological activities of traditional oriental medicines.…”
Section: The Effects Of Fermented Foods On Cognitive Functionmentioning
confidence: 99%
“…In this study, we compared the commonly used inbred C57BL/6 mouse strain with the outbred ICR mouse strain to rationalize the effect of genetic variation. While abundant scientific research has used the C57BL/6 mouse strain as a general model for neurodegenerative disorders [ 16 , 17 , 18 ], continued breeding eventually results in the development of two genetically-distinct sub-strains: the C57BL/6J (Jackson Laboratory) and the C57BL/6N (National Institute of Health). Thus, we extended our study to compare these two sub-strains in order to obtain a clearer picture of behavioral and cognitive stability.…”
Section: Introductionmentioning
confidence: 99%